Kinetic Modelling of Sonocatalytic Phenol Degradation over Alumina-Supported Copper Oxide Catalyst - YAHAYA, Abdullahi; ADO, Ahmad; MUHAMMAD, Jaju A.; SANI, Zaharaddeen G.; OLUWA, Baba A.; YUSUF, Abdulazeez A. (FUDMA Journal of Engineering and Technology, 2026)
Phenol is a toxic organic pollutant often found in industrial wastewater, and its resistance to conventional treatment has made it a key target for advanced oxidation processes. In this study, a 9 wt% CuO/Al₂O₃ catalyst was prepared by incipient-wetness impregnation and evaluated for sonocatalytic phenol degradation in the presence of hydrogen peroxide. The catalyst was characterized using X-ray diffraction, nitrogen adsorption–desorption analysis, and scanning electron microscopy. The results confirmed the formation of CuO species on alumina, with preserved surface area, pore volume, and accessible surface morphology. Phenol degradation was investigated under ultrasound irradiation by varying H₂O₂ concentration, catalyst dosage, initial pH, and temperature. Sole sonolysis showed low degradation efficiency, reaching only about 8 % after 100 min. The addition of 9Cu/A and H₂O₂ greatly increased phenol removal, with optimal performance obtained at 30 mM H₂O₂, 20 g/L catalyst dosage, pH 4, and 70 °C. Excess H₂O₂ or catalyst loading lowered degradation due to radical scavenging and ultrasonic wave attenuation. Kinetic analysis showed that phenol degradation followed an apparent pseudo-first-order model, with a rate constant of approximately 0.0331 min⁻¹ under optimal conditions, compared with about 0.0008 min⁻¹ for sonolysis with H₂O₂ alone. The findings show that CuO/Al₂O₃ promotes H₂O₂ activation and strengthens sonochemical phenol oxidation.